Shallow water fish display low phenotypic plasticity to ocean warming and extreme weather events regardless of previous thermal history - Missionário, Madalena (2024)
Shallow water environments have long been recognized by scientists as sentinels for climate change. By analysing the impacts of ocean warming and marine heatwaves (MHW) in species from these areas, we can estimate their plasticity and hence vulnerability to thermal challenges. Pomatoschistus microps is a benthic intertidal fish species inhabiting coastal lagoons where temperature fluctuations are common. Here, we tested the effects of " Present " and " Future summer" scenarios (22 degrees C and 25 degrees C) and their respective heatwaves (27 degrees C and 30 degrees C) versus a " Control " scenario of 19 degrees C on warm (summer)- and cold (winter)- acclimatized fish. Then, we estimated phenotypic plasticity of critical thermal maximum (CTmax), oxygen consumption and cellular stress responses (CSR). Temperature seasonal variation and body weight (as proxy for body size) effects on fish thermal tolerance were also determined. Fish exposed to higher temperature treatments exhibited higher thermal tolerance, with this pattern being consistent for both warm- and cold-acclimatized fish. However, this difference was subtle (<4.6 %), suggesting a low capacity for acclimation. Nonetheless, warm-acclimatized fish (collected in summer) displayed significantly higher CTmax than cold-acclimatized fish (collected in winter), indicating that CTmax is influenced by seasonal thermal variation. Weight also represents a constraint factor for P. microps thermal tolerance, as heavier animals displayed lower CTmax. No alterations in O2 consumption, neither in CSR biomarkers were detected across temperature treatments, suggesting that fish were otherwise relatively insensitive to thermal fluctuations, independently of thermal history, within the thermal scenarios tested. Overall, the studied population of P. microps seems well adapted to temperature variations in their natural environment, exhibiting a large thermal safety margin (average of 11.02 degrees C).